An anisotropic hyperelastic constitutive model for short glass fiber-reinforced polyamide. (September 2016) - Chebbi, E.; Wali, M.; Dammak, F.
Abstract: The present paper describes the development of a unified hyperelastic constitutive model based on anisotropic hyperelastic material with families of fibers approach and integrating both; pure isotropic matrix of polyamide-6.6 and anisotropic materials induced by the short glass fiber reinforcement (SGFR), into one framework. The material model is implemented in a four-node shell element. The model is used to predict the mechanical behavior of SGFR polyamide-6.6. Material parameters are identified using experimental data from tensile tests on unreinforced and 10, 20, and 30% wt reinforced, polyamide-6.6. The proposed model is validated with two points bending experimental results. Experimental and finite elements results are compared. Numerical results prove the good performances of the developed model to predict the anisotropic behavior of SGFR polyamide-6.6.